Development of Moral Education in Students Through Religious Extracuriculars in Senior High Schools - Oktarinda, Oktarinda; Ulawal, Romi; Wulandari, Wulandari; Musfiroh, Wardiyatun (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2021)
The cultivation of moral education is not only implemented in class subject matter, but can be implemented in extracurricular activities at school. Each school has extracurricular activities including religious activities. In fact, the cultivation of moral education can be carried out in religious extracurricular activities. This study aims to explore whether the form of the activity, description of the implementation, and the results of the activity. This research was written using a qualitative method with a case study type. Sources of data were taken through direct interviews with ten informants using a set of interview protocols. The informants consisted of student representatives, extracurricular coaches and students who took part in the activity. All interview results were analyzed thematically using the Miles and Huberman technique. The research findings found three forms of high school religious extracurricular activities, namely; i) Anisa forum, ii) memorizing the Qur’an, iii) regular religious lectures. The implementation of religious extracurricular activities is in accordance with a predetermined schedule. The results of cultivating religious extracurriculars on the moral education of students have succeeded in finding the results of each form of activity, namely; i). good and true and happy in studying religion. The findings of this study can be used as initial data for subsequent researchers to examine the problems of this research in different contexts and issues.